The Application of Value Engineering-Based Balanced Scorecard on Madura Small and Medium Enterprises: A Customer-Oriented and Cost- Efficiency Strategic Approach - Fais, Moh. Ainul; Deviyanti, I Gusti Ayu Sri; Widari, Nyoman Sri; Tjandra, Suhatati (Universitas Teuku Umar, 2025)
Madura stalls, as part of informal micro-enterprises, play a vital role in meeting the needs of urban communities. However, most still operate without a structured strategic management system and performance measurement. This situation makes it difficult for business owners to monitor efficiency, understand customer satisfaction, and plan for long-term competitiveness. On the other hand, there is a research opportunity to adapt modern management methods, such as the Balanced Scorecard (BSC) and Value Engineering (VE), to suit the context of simple yet influential small businesses. This study aims to design a performance measurement system by integrating VE into the BSC framework at a Madura stall in Klampis, Surabaya. The method used is an exploratory case study with a mixed-methods approach, involving owners (n = 5), employees (n = 10), and customers (n = 30). Data were collected through interviews, observations, questionnaires, and document review. Data were then analyzed using the Function Analysis System Technique (FAST), KPI formulation, AHP weighting, and performance evaluation. The study results show that several key performance indicators exceeded targets, such as daily sales volume (226.7%), number of customers (200%), and net profit (120%). These achievements confirm that the integration of the BSC and VE can improve cost efficiency, strengthen customer orientation, and provide a clearer strategic direction for informal micro-enterprises. This study contributes by providing a contextually relevant performance measurement framework and opens up opportunities for further research on the application of the BSC and VE to other micro-enterprise units.